EFFICIENCY THRESHOLD CRITERION IN COUPLING FORKED MOVING CONTACTS CIRCUIT BREAKERS AND CURRENT LIMITING REACTORS (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
This paper establishes the efficiency threshold criterion for the use of forked moving contacts on power circuit breakers (CBs) to enhance parallel operation of circuit breaker/current limiting reactor that approximates series short-circuit current limiting reactor connection with no constant power losses [1, 2]. It provides adequate guide for selecting appropriate Current Limiting Reactor (CLR) inductance (reactance) for an efficient power circuit breaker operating mechanism energy requirement and cos